A Theoretical and Policy Approach of Clusters, as Supporting Innovation and Development - Andrei, Dalina Maria (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2014)
The concept of Clusters seems to belong to the present whereas actually it is an old economic concept. Even classics (e.g. David Ricardo) or old neoclassic (e.g. Alfred Marshall) have still significant references for the today, whereas present produced enough favorable environment for. This paper will develop some of all references about, economic thinking, description and policy issues to be noted on. Moreover, the new need of clusters consists in the scenery that the economy exposes and preserves today. Risks, disadvantages and all that shadow such new current character and actor‟ are not only inherent, but keep their place in context. The specific cluster policy, in its turn, explicitly identifies what the national level‟s interests and the barriers of achieving those goals are and how cluster approach can help overcome these problems. It equally weights the relative merits of active intervention from the national level, versus framework conditions and facilitation, vis-à-vis theories and models.